Marketing cultural desenvolvidos pelas empresas: O valor cultural e mercadológico dessa aproximação. - Zenone, Luiz Claudio (2005)
The practice of cultural marketing has been presented as an alternative for the society into a context of which the retraction of the State occurred as a great supplier of social demands. It is important to establish a distinction between the company, which really practices it as an exercise of social responsibility and that, which takes advantage of more than one marketing action, aiming to create a value for the institutional trademark. In this study, it was observed that it is not enough to invest in cultural actions when the other activities of the company have many harmful effects to the society, resulting in the invalidation of the benefits generated by this pseudopractice. Thus, the approach of companies with cultural activities may not be disassociated of concepts of social responsibility and organizational ethic. The comprehensive practice of the cultural marketing may have a positive influence on the three following aspects: social, economic and marketing. Therefore, to invest in cultural marketing must be part of a long-term strategy of less immediatist action companies with concerns beyond the profit of this practice or with interests related to fiscal investment incentives given by the government to those who invest in cultural activities. In accordance with this study, the society (mainly, the consumers inserted on it) has a fundamental role to lead the practice of social responsibility based on the investment of cultural actions. In our research another factor could be observed as the union of efforts of the three sectors of the society represented by the state, enterprises and civil society aiming to emphasize the impact of the developed actions. Finally, it was observed that the cultural marketing does not guarantee that the society could differentiate the company aiming social actions from those using the concept of marketing practices